Arabidopsis lyrata Small RNAs: Transient MIRNA and Small Interfering RNA Loci within the Arabidopsis Genus([W])([OA]) - Ma, Zhaorong (American Society of Plant Biologists, 2010)
Twenty-one-nucleotide microRNAs (miRNAs) and 24-nucleotide Pol IV-dependent small interfering RNAs (p4-siRNAs) are the most abundant types of small RNAs in angiosperms. Some miRNAs are well conserved among different plant lineages, whereas others are less conserved, and it is not clear whether less-conserved miRNAs have the same functionality as the well conserved ones. p4-siRNAs are broadly produced in the Arabidopsis genome, sometimes from active hot spot loci, but it is unknown whether individual p4-siRNA hot spots are retained as hot spots between plant species. In this study, we compare small RNAs in two closely related species (Arabidopsis thaliana and Arabidopsis lyrata) and find that less-conserved miRNAs have high rates of divergence in MIRNA hairpin structures, mature miRNA sequences, and target-complementary sites in the other species. The fidelity of miRNA biogenesis from many less-conserved MIRNA hairpins frequently deteriorates in the sister species relative to the species of first discovery. We also observe that p4-siRNA occupied loci have a slight tendency to be retained as p4-siRNA loci between species, but the most active A. lyrata p4-siRNA hot spots are generally not syntenic to the most active p4-siRNA hot spots of A. thaliana. Altogether, our findings indicate that many MIRNAs and most p4-siRNA hot spots are rapidly changing and evolutionarily transient within the Arabidopsis genus.